An integrin from oyster Crassostrea gigas mediates the phagocytosis toward Vibrio splendidus through LPS binding activity. Issue 1 (November 2015) - Jia, Zhihao; Zhang, Tao; Jiang, Shuai; Wang, Mengqiang; Cheng, Qi; Sun, Mingzhe; Wang, Lingling; Song, Linsheng
Abstract: Integrins are a family of cell adhesion molecules which play important roles in the regulation of cell adhesion, migration, proliferation, apoptosis and phagocytosis. In the present study, the immune function of an integrin from the oyster Crassostrea gigas (designated Cg Integrin) was characterized to understand the regulatory mechanism of hemocyte phagocytosis toward different microbes. The full-length cDNA of Cg Integrin was 2571 bp with an open reading frame (ORF) of 2397 bp, encoding a polypeptide of 799 amino acids. The mRNA transcripts of Cg Integrin were predominantly detected in hemocytes, gonad and adductor muscle, while lowly in hepatopancreas, mantle and gill. The mRNA expression level was up-regulated at 6 h post lipopolysaccharide (LPS) stimulation ( p  < 0.01), while no significant change was observed after peptidoglycan (PGN) stimulation. The oyster hemocytes with relative high Cg Integrin expression level exhibited different phagocytic abilities towards different microorganism and particles, such as Gram-positive bacteria Vibrio splendidus, Gram-negative bacteria Staphylococcus aureus and latex beads. Moreover, the phagocytic rate towards V. splendidus was significantly decreased after the blockade of Cg Integrin using the polyclonal antibody. The recombinant Cg Integrin (r Cg Integrin) displayed agglutinating activity towards V. splendidus but not S. aureus and Y. lipolytica. It also exhibited a higher binding affinity towards LPS (compared to rTrx group) in a dose-dependent manner with the apparent dissociation constant ( K d ) of 5.53 × 10 −6  M. The results indicated that Cg Integrin served as a pattern recognition receptor with LPS binding activity, which could directly bind to V. splendidus and enhance the phagocytosis of oyster hemocytes. Highlights: Cg Integrin was a β-Integin form oyster Crassostrea gigas. Cg Integrin was significantly up-regulated post Gram-negative bacteria challenge. CgIntegrin was expressed on the membrane of different hemocytes. Integrin hi hemocytes displayed different phagocytic abilities towards diverse microorganisms. Cg Integrin had LPS binding activity and could directly bind to V. splendidus .